2022
DOI: 10.2166/ws.2022.377
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic nitrate contamination of water resources in Ethiopia: an overview

Abstract: Nitrate is one of the water contaminants that mainly result from anthropogenic activities. The major causes of nitrate contamination of water resources are anthropogenic activities such as animal or human waste, septic or sewage systems, fertilizer application, concentrated animal farming, industrial waste, and landfill leachates. These man-made activities are the primary sources of nitrate contamination in water resources. Nitrate contamination of water is a global issue that has been increasing over time. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…This investigation stepped back decades ago [ 9 , 10 ], pointed out that how the present groundwater resource could be vulnerable to significant pollution risks due to the continued population growth, agricultural expansions and the concomitant increased demands [ 11 ]. Recent studies [ [12] , [13] , [14] , [15] , [16] , [17] ] confirmed the fact that groundwater contamination peril is in existence.…”
Section: Introductionmentioning
confidence: 89%
“…This investigation stepped back decades ago [ 9 , 10 ], pointed out that how the present groundwater resource could be vulnerable to significant pollution risks due to the continued population growth, agricultural expansions and the concomitant increased demands [ 11 ]. Recent studies [ [12] , [13] , [14] , [15] , [16] , [17] ] confirmed the fact that groundwater contamination peril is in existence.…”
Section: Introductionmentioning
confidence: 89%
“…The materials synthesized in this study showed higher recyclability when compared to activated carbon from bamboo sawdust-derived where the paracetamol removal efficiency drops to the range of 88% after 5 cycles. 146 Despite exhibiting lower removal efficiency compared to CAF, the hierarchically porous carbons proved to be excellent adsorbents for the evaluated contaminants.…”
Section: Adsorption Of Parmentioning
confidence: 95%
“…According to the literature, the possible interactions and mechanisms involved in the adsorption of paracetamol using carbon materials as adsorbents are: hydrogen bonds between the phenolic and carboxylic groups of HPCs with paracetamol, electrostatic interactions (ion-dipole), and the p-p type interactions (aromatic rings of HPCs with PAR). 145,146 Fig. 4 illustrates all possible adsorption mechanisms for paracetamol.…”
Section: Adsorption Of Parmentioning
confidence: 99%
“…According to WHO [7], 2 billion people use or consume water polluted with fecal coliforms, nitrates and/or toxic metals. The consequences of consuming polluted water are reflected in a negative impact on human health through water diseases, such as cholera, dysentery, typhoid fever, salmonellosis, diarrhea, blue child syndrome or methemoglobinemia, gastric cancer, congenital disabilities, dental and skeletal fluorosis, cardiovascular disease, renal, and pulmonary [8][9][10][11][12][13][14][15][16][17]. Worldwide, 435 million people drink from unprotected wells and springs; there are 4 billion cases of gastrointestinal diseases and 1 million deaths in children under 5 years of age due to diarrheal diseases; hence, health risk-related research is transcendental in several countries around the world.…”
Section: Introductionmentioning
confidence: 99%